Planeación estratégica de tecnología informática de la empresa Moderna Alimentos S.A. - Toapanta Tamayo, Marco Roberto (2016)
This degree dissertation proposes to apply the Information Technology Strategic Plan (PETI for its acronym in Spanish) for Moderna Alimentos Enterprise. Nowadays the technology needs must be taken to another level and not only focus on support, and should seek to align their strategies area with the business. First of all the reasons that prompted the implementation of this study and methodology, the objectives of the company and its justification are reviewed. In addition, all the theoretical part surrounding the above referenced methodology as well as the guidelines that support the further development of this project are explained. In the second chapter, Moderna Alimentos Enterprise is fully described, the line of business and its evolution over the years that have led the company to be at the top in the production of flour and wheat products are known.